PKM (Pengabdian Kepada Masyarakat) Penyuluhan Tentang Pemanfaatan Pakaian Bekas Menjadi Produk Baru (Lenan Rumah Tangga) Di Panti Asuhan Al Manar Desa UjunggurapKecamatan Batunadua Kota Padangsidimpuan Sumatera Utara - Butar-butar, Khairunnisa; Harahap, Olivia Feby Mon (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Exploring potential and seeking opportunities, especially from the economic sector and creative industry must be done by upgrading capabilities and skills, to be managed again. One of them is the use of used clothes into new products, which will be carried out in this mentoring process. With the aim that the community is able to find and process used clothes that are owned into new products that have new benefits and are of sale value. The learning method used is two-way communication (instructors and participants) by doing demonstrations, practice and evaluation. The teaching materials used are handouts and presentation media (PPT), leaflets, LCD, In focus, sound system. Meanwhile, the tools and materials used are used t-shirts, scissors, and hand needles and sewing threads. The result of this activity is the enthusiasm of the students / participants in managing used clothes by seeing the results of practice based on their respective ideas. With the results of the product and the positive response from this activity, it was seen that the students / participants were interested in re-developing products from used clothes with follow-up meetings / activities.